The Role of Transformational Leadership in Enhancing Employee Performance: A Systematic Literature Review - Ahmad Hadi Saptaji; Ismail Nurdin (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
The success of bureaucratic reform in Indonesia depends heavily on the performance of civil servants (ASN) as the primary providers of public services, with leadership recognized as one of the key determinants of that performance. Transformational leadership is regarded as genuine leadership, as it directs organizations toward goals never previously achieved, in contrast to leadership styles that merely preserve the status quo. This study aims to examine the influence of transformational leadership on improving employee performance through a Systematic Literature Review (SLR) approach. Data were collected by searching for articles on Google Scholar using the keyword "Transformational Leadership and Employee Performance," yielding 10 selected articles published between 2019 and 2025 for in-depth review and analysis. The findings show that transformational leadership consistently has a positive and significant effect on employee performance, in both government institutions and private companies. This effect occurs both directly and indirectly through several mediating variables, namely work discipline, job satisfaction, work motivation, organizational culture, and job autonomy. Transformational leadership has been shown to inspire, motivate, and develop subordinates' potential, thereby increasing commitment, loyalty, trust, and employee engagement in achieving organizational goals. Accordingly, implementing transformational leadership is an effective strategy for improving organizational performance in both public and private sectors, while also supporting the success of the bureaucratic reform agenda through strengthening the quality of civil servants.